Impact of Different Therapeutic Protocols on Blood Biochemical Markers and Fertility in Anestrus Sahiwal Cows - Husain, Safayat; Kumar, Rajesh; Singh, Bhoopendra; Srivastava, Sushant; Kumar, Rabindra; Kumar, Pramod; Haque, Nilufar (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
Bovine anestrus syndrome is a multifactorial disorder of the reproductive system. The problem is severe in suburban and rural areas of  the country. The present study was aimed to evaluate the effect of different therapy on biochemical parameters and fertility response  in 24 anestrus Sahiwal cows. Anestrus cows were randomly divided into four equal groups of six animals each, and were subjected with  Lugol’s iodine 2%, cervical painting with per rectal massage of genitalia thrice on alternate day (G1, n=6), XXX herbal bolus 1 bid for  2 days, repeated on day 11 & 12 later in non-respondents (G2, n=6), and modified ovsynch protocol which consisted of 100 mg hydroxy  progesterone caproate injected daily s/c for 6 days followed by inj. GPG (G3, n=6), while one group was kept as untreated control  (G4, n=6). Blood samples were collected thrice from all cows, i.e., pretreatment day-0 (S1); post-treatment at induced estrus/AI (S2) and  day 21 post-AI (S3), for estimation of serum progesterone and biochemical constituents. In general, except progesterone, the mean  values of serum glucose, total cholesterol, total protein, albumin, calcium and phosphorus were significantly (p
Keywords: Anestrus; Biochemical parameters; Estrus induction; Sahiwal cows; Therapy